Assessment of hydrogen and nanoparticles blended biodiesel on the diesel engine performance and emission characteristics. (1st January 2022) - Zhang, Xiumei; Yang, Rui; Anburajan, Parthiban; Le, Quyet Van; Alsehli, Mishal; Xia, Changlei; Brindhadevi, Kathirvel
Graphical abstract: Highlights: Effects of nanoparticles and hydrogen was examined. Performance and emission characteristics were measured for constant H2 flow rate. Addition of the hydrogen enhanced the torque and brake thermal efficiency. No significant reduction on NOx reported despite the H2 addition. Abstract: Owing to the greatest need and continuous requirement of the fossil fuel, the immediate search of alternate resources to the petroleum fuel is essential. This research deals with the production and utilization of waste cooking oil biodiesel and nanoparticles blends in the direct ignition engine. The nanoparticles added blends was then reinforced with hydrogen flow while conducting the tests. The fuel blends used for the tests were D100 (pure diesel), B10 (90% diesel + 10% biofuel), B20 (80% diesel + 20% biofuel), D100T10 (pure diesel with 100 ppm nanoparticles), B10TH (90% diesel + 10% biofuel with 100 ppm nanoparticles + 5 L/min of H2 ) and B20T10 (80% diesel + 20% biofuel with 100 ppm nanoparticles + 5 L/min of H2 ). While conducting the tests, the hydrogen flow was given at the constant mass flow rate of 10 L/min. The performance and emission measures were keenly calculated from the tests. All tests were conducted at different speeds from 1800 rpm to 2800 rpm. The performance parameters were improved by these nanoparticles and hydrogen together with the pure diesel and also with the biodiesel blends. For example, the power, torque and brake thermal efficiency were improved while the brake specific fuel consumption was decreased. The main objective of reducing the emission of CO, CO2 and other UHC was satisfied whereas the NO emission was slightly increased.